Value of foetal umbilical vein standardised blood flow volume in predicting weight gain in the third trimester: a prospective case-cohort study - Fang, Qian; Shi, Yihao; Zhang, Chao; Cai, Ying; Yuan, Cuili; Yang, Jiaxiang; He, Guannan (Frontiers in Pediatrics, 2024)
Objective: This study aims to establish a prediction model of foetal umbilical vein standardised blood flow volume (sQuv) on estimated foetal weight (EFW) in the third trimester.: A case-cohort study involving 200 eligible normal foetuses was conducted at the Ultrasound Department of Longquanyi District of Maternity and Child Healthcare Hospital between June 1, 2020 and December 31, 2021. Ultrasound measurements were taken at two separate intervals to assess EFW and the rate of EFW (rEFW) (first: between 28 w-33 w6d of gestational age [GA]; second: after 4-6 weeks). Umbilical vein blood flow volume (Quv) and sQuv (normalised with EFW) were calculated only during the initial measurement. Using general linear regression, a prediction model for EFW based on GA and sQuv was developed, with the gestational week employed as a calibration scalar and validated using linear regression cross-validation.Results: In the third trimester, EFW exhibited significant correlations with GA, abdominal circumference (AC), head circumference (HC) and Quv (all ρ > 0.6, P < 0.001). Furthermore, the rEFW showed significant correlations with Quv and sQuv (all ρ > 0.6, P < 0.001). A linear regression equation was established using a general linear regression model: rEFW = 0.32689 × sQuv. Additionally, a foetal weight prediction model (EFW = -2554.6770 + 0.9655 × sQuv + 129.6916 × GA) was established using sQuv. The above two formulas were cross-validated by intra-group linear regression and proved to be of good efficacy.In the third trimester, EFW displayed significant correlations with GA, AC, HC and Quv. Additionally, the rEFW exhibited significant correlations with Quv and sQuv. The sQuv during the third trimester has predictive value for foetal weight, serving as an early warning indicator.